Country Effect. Location of Foreign Direct Investments in the European Union Countries - Magdalena Kinga STAWICKA (Communications of International Proceedings, 2021)
Progressive integration, globalization, foreign trade liberalization, free capital flow, development of new IT technologies and new means of transport resulted in expansion of enterprises into foreign markets. The aim of this paper shall be examination of factors which have an impact on unequal deployment of foreign direct investments (FDIs) in European Union (EU) countries. In order to achieve the desired goal, the author shall conduct analysis of FDIs’ location based on the selection of variables which in the literature of the subject, have been recognized to be potentially correlated with inflow of the FDIs. At the next stage, the author shall try to understand whether and to what extent the ability of a country to attract the FDI is strengthened or hampered by so-called “country effect”, which can take two different forms. After identification of the “national” (domestic) and the “regional” factors, which attract the FDI, it shall be possible to implement more effective FDI promotion policies at the national, regional, and sectoral levels. A basic regression model enables spatially weighted exogenous variables to capture the third country effects of bilateral FDI, and moreover, spatial correlation to control the transmission of (potential) shocks across host countries.
Keywords: foreign direct investments (FDIs); spatial distribution of FDI; country effect; spatial econometrics